Relatório de estágio curricular obrigatório: área de clínica cirúrgica de pequenos animais - Pitol, Charline Alecsandra (My University, 2025)
This report aims to present the activities carried out during the mandatory curricular internship in Veterinary Medicine, conducted in the complex surgery unit of the Veterinary Teaching Hospital at the Federal University of Santa Maria (HVU-UFSM). The internship was supervised by Veterinary Physician Prof. M.Sc. Manoela Maria Bianchi and overseen by Veterinary Physician Prof. Dr. PhD Maurício Veloso Brun. It was carried out from March 5 to May 23, 2025, totaling 460 hours. Over this period, 94 patients were monitored, the majority being dogs (80%) and females. A total of 313 practical activities were recorded, including outpatient and anesthetic procedures, complementary exams, and general tasks. The most frequently performed actions included surgical antisepsis (13.74%), vital signs monitoring (13.42%), and venous catheterization (13.42%). Additionally, 79 procedures were carried out in the surgical center, along with 18 clinical-surgical consultations and 14 sessions of hyperbaric oxygen therapy. The experience in the complex surgery unit provided extensive exposure to challenging cases and advanced techniques, contributing significantly to the student's technical, scientific, and personal development. This report also includes two case studies followed during the internship: one case of patent ductus arteriosus (PDA) in a male Spitz dog, and a right adrenalectomy performed via videolaparoscopy in a female Shih Tzu. Both cases represented valuable opportunities for practical learning in the surgical field. [resumo fornecido pelo autor]
O presente relatório tem como objetivo apresentar as atividades desenvolvidas durante o estágio curricular obrigatório em Medicina Veterinária, realizado no setor de cirurgias complexas do Hospital Veterinário Universitário da Universidade Federal de Santa Maria (HVU-UFSM). Foi orientado pela Média Veterinária Profa. Me. Manoela Maria Bianchi e supervisionado pelo Médico Veterinário Prof. Dr. PhD Maurício Veloso Brun, sendo realizado no período de 05 de março a 23 de maio de 2025, totalizando 460 horas. Ao longo do período, foram acompanhados 94 pacientes, sendo a maioria cães (80%) e fêmeas. No total, registraram-se 313 atividades práticas, incluindo procedimentos ambulatoriais e anestésicos, exames complementares e atividades gerais. As ações mais frequentes envolveram antissepsia cirúrgica (13,74%), aferição de parâmetros vitais (13,42%) e venóclise (13,42%). Também foram realizados 79 procedimentos no centro cirúrgico, 18 atendimentos clínico-cirúrgicos e 14 sessões de oxigenoterapia hiperbárica. A experiência no setor de cirurgias complexas proporcionou amplo contato com casos desafiadores e técnicas avançadas, contribuindo significativamente para o desenvolvimento técnico, científico e pessoal da aluna. O relatório inclui, ainda, dois relatos de caso acompanhados ao longo do estágio: um caso de persistência do ducto arterioso (PDA) em um cão da raça Spitz Alemão e uma adrenalectomia direita videolaparoscópica em um cão da raça Shih Tzu, ambos representando oportunidades valiosas de aprendizado prático na área cirúrgica. [resumo fornecido pelo autor]
Keywords: Medicina veterinária; Clínica médica; Cirurgia veterinária; Hospitais veterinários; Animais - Doenças - Tratamento